2008
DOI: 10.1080/03079450801986529
|View full text |Cite
|
Sign up to set email alerts
|

A reverse transcriptase-polymerase chain reaction survey of infectious bronchitis virus genotypes in Western Europe from 2002 to 2006

Abstract: A survey of infectious bronchitis virus (IBV) genotypes in poultry flocks in selected countries in Western Europe was carried out between March 2002 and December 2006. Identification of IBV was by reverse transcriptase-polymerase chain reaction of RNA extracted from oropharyngeal swabs taken from poultry flocks exhibiting signs of clinical disease thought to be attributable to IBV. Part of the hypervariable S1 gene of IBV was sequenced to differentiate between the various genotypes. During the survey, 4103 sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
192
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(203 citation statements)
references
References 31 publications
9
192
1
1
Order By: Relevance
“…The AvCoV-IBV isolates detected in this study were found to be similar to IBV isolates detected in Israel, Turkey, Iraq, Jordan, and Egypt like strains KF179074, HM802259, EU780077, JX027070, JX173488, and KF153245, but different from IBV isolates QX and Italy-02 (EU780077) (1,15,23,29), detected in other European countries. The predominance of IBV genotypes representing isolates belonging to Asian-type lineages, found in this study, suggests that Turkey has more cross-border poultry trade with Middle Eastern countries than with European countries.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The AvCoV-IBV isolates detected in this study were found to be similar to IBV isolates detected in Israel, Turkey, Iraq, Jordan, and Egypt like strains KF179074, HM802259, EU780077, JX027070, JX173488, and KF153245, but different from IBV isolates QX and Italy-02 (EU780077) (1,15,23,29), detected in other European countries. The predominance of IBV genotypes representing isolates belonging to Asian-type lineages, found in this study, suggests that Turkey has more cross-border poultry trade with Middle Eastern countries than with European countries.…”
Section: Discussionsupporting
confidence: 67%
“…Amongst the IBV strains identified in the broiler flocks, 17.2% represented the detection of the IBV Ma5 and H120 vaccine strains (95.6%-99.2%) and 48.9% represented the Israel variant 2 isolate (94.8%-99.4%), whereas all of the layer flock-derived sequences were represented in the 4/91 vaccine strain (96.2%-99.5%). Results from field surveys for assessing the presence of IBV in chickens in Western Europe showed 59% positive for AvCoV-IBV with about 50% of the positive samples representing identification of vaccine strains (29). Similarly, vaccine strains were also detected following the assessment of poultry in the Middle East for the presence of IBV (13,19,25).…”
Section: Discussionmentioning
confidence: 99%
“…Extracted RNA was subjected to RT-PCR to detect a 393 bp partial-S1 sequence in the hypervariable region of the S1 gene (Awad et al, 2014;Cavanagh et al, 1999;Ganapathy et al, 2015;Worthington et al, 2008). In previous genotyping studies, this region was targeted due to the increased genetic variation possibilities.…”
mentioning
confidence: 99%
“…In a previous study, we identified strains of the 793B genotype, which are the same as the 4/91 vaccine strain, as a new variant in Japan [20]. In Japan, field isolates of 793B had not been isolated until 2003, but IBVs of 793B have been widely isolated in several European countries since 1991 [4,8,23].…”
Section: Discussionmentioning
confidence: 99%